Validation of Revised Baveno VI Criteria for Screening of Varices Needing Treatment in Children with Cirrhosis - Samanta, Tryambak (Clin Exp Gastroenterol, 2020)
BACKGROUND: Baveno VI criteria for screening varices needing treatment (VNT) have not yet been validated in an exclusive pediatric and adolescent set of the population, in whom baseline parameters differ in relation to adults. Therefore, our primary objective was to validate Baveno VI and its expanded form in children below 18 years of age. The secondary aim was to elicit whether any revision of the above criteria with a target of not missing more than 5% VNT could be more accurate for this age group. MATERIALS AND METHODS: The work was carried out in two medical institutes, over a span of 3 years. Consecutively enrolled patients below 18 years of age, with compensated cirrhosis confirmed by liver biopsy, were evaluated for related blood parameters, transient elastography (TE) and esophagogastroduodenoscopy. RESULTS: Out of the 33 recruited patients, five (15.15%) met the criteria for VNT. The sensitivity, specificity, PPV and NPV of Baveno VI and Expanded Baveno VI were observed as 60%, 92.3%, 60% and 92.3%, and 20%, 100%, 100% and 88%, respectively. We found that the Revised Baveno VI criteria with TE <19 kPa and platelet count of >175×10(9) cells/L, with sensitivity 100%, specificity 79%, PPV 45%, NPV 100% and accuracy of 82%, are more appropriate for this age group. CONCLUSION: We propose that further multicentrer studies with a larger sample size should be conducted before incorporating Revised Baveno VI criteria for high-risk varices in patients below 18 years in future guidelines.